STUDI KAJIAN DALAM AL-QUR’AN - Hayati Nupus; Wafiz Ajiza (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
The Koran is a book that was revealed by Allah SWT to the Prophet Muhammad SAW. Through the angel Gabriel to be conveyed to humans. The Koran is also a source of Islamic teachings and a guide to life for mankind. The Al-Quran itself consists of 30 chapters, 114 letters and 6666 verses which were revealed mutawatir. The Al-Quran begins with the Al-Fatihah surah and ends with the An-Naas surah, which is a Makkiyah surah. The Qur'an is the word of Allah SWT which is a guide as well as a legal basis for humans in achieving happiness in this world and in the afterlife. Starting from the time of Prophet Adam AS to Prophet Muhammad SAW, messengers of Allah SWT came to convey God's teachings to his people. Because the Qur'an is a guide for humans in organizing their lives, in order to obtain physical and spiritual happiness, in this world and the hereafter. The function of the revelation of the Qur'an is as a guide for humans and as explanations regarding that guidance. Apart from that, it is also a distinction between what is right and what is false. There is no doubt in the Qur'an for devout believers who always want to receive guidance from Allah in their lives. The Qur'an is the sentence of Allah which is perfectly true and just in its content. Nothing can change Allah's sentences. The Al-Quran is the word of Allah revealed by the Prophet Muhammad SAW, who is the Prophet of the end times, through the angel Gabriel as a miracle. The Al-Quran is a source of knowledge for Muslims which is the legal basis that covers everything, both regarding religious law and social aspects in everyday life.